Os impactos da COVID-19: um estudo com alunos de famílias da agricultura familiar do município de Santa Helena-PR - Silva, Cristina Elisabete Prediger Nonato da (2022)
During the COVID-19 pandemic, several tools were used to adapt predominantly faceto-face teaching to remote teaching. Schools, teachers, students and families wererequired to make structural changes in family and social life, which faced different challenges according to their context. In this bias, the present research aims to verify how the children of small rural farmers in the Municipality of Santa Helena - PR continued their studies remotely during the pandemic. Thus, to justify how it developed, the learning process of the students of the Pedro Álvares Cabral Municipal School, who came from family farming during the COVID-19 pandemic, was questioned. We selected a school from the municipal education network whose inclusion criteria were the school from the districts with the best IDEB, students from families that are part of family farming who reside in the district of São Roque and study in the 5th year of the Municipal School Pedro Álvares Cabral. The methodology focus-es on case study, qualitative, there were several students, the method of approach is phenomenological through a questionnaire prepared for this research. The data collection instruments were the questionnaire and the Paraná test. The results indicate that studying without the presence of the teacher was bad for most students. When asked if they liked remote teaching, 76.93% claimed that it was difficult to study without the teacher and they missed their friends, only 23.07% of students liked re-mote teaching, as they could help their parents, play and play. The fact of not having to wake up early, having more time to play and spend time with the family was high-lighted by 10 students interviewed. Of the 40 students belonging to the classes, 13 belonged to family farming, scored as negative the fact of having to wear a mask and not being able to see friends, reported that their school performance was better before the pandemic, thus preferring face-to-face teaching to remote teaching. They commented that they found it easier in the disciplines of Art and Physical Education, followed by Mathematics and Portuguese, however, they had more difficulty in the disciplines of Science, Entrepreneurship and Citizenship. The results obtained in the Paraná test held in 2021 show that students were better in the subjects of Portu-guese Language and Mathematics, obtained an average of less than 53% of correct answers in the subject of History, the average of correct answers in Sciences of Na-ture and Geography was 67 % corroborating their perception of performance in the study. Despite the study difficulties, it was possible to perceive that the reflection of the IDEB of 2021, the students were close to the average of the IDEB of 2020, per-haps the reason is due to the implementation of the Project “Recovery and accelera-tion of learning”, with strategies and interventions, increase of the workload of teachers and students, with the aim of recovering post-pandemic content. In gen-eral, farming families had difficulty with teaching related to problems with the tech-nology needed for teaching, although this fact was not verified with emphasis. Some students highlighted as a positive aspect the fact of being able to contribute to work and help their family in the field.